Compact cosmic ray detector for unattended atmospheric ionization monitoring. - Aplin, K; Harrison, R (2010)
Two vertical cosmic ray telescopes for atmospheric cosmic ray ionization event detection are compared. Counter A, designed for low power remote use, was deployed in the Welsh mountains; its event rate increased with altitude as expected from atmospheric cosmic ray absorption. Independently, Counter B's event rate was found to vary with incoming particle acceptance angle. Simultaneous co-located comparison of both telescopes exposed to atmospheric ionization showed a linear relationship between their event rates.